The prevalence and determinants of female serodiscordance among HIV positive pregnant women attending PMTCT clinic in Owerri, Imo state, Nigeria - Eze, Innocent O.; Okeudo, Chijioke; Ezem, Bamidele U.; Ukoh, Clara U.; Nzeribe, Emily A.; Nwagha, Uchenna; Njoku, Tobechi; Uzoma, Onyeka; Duke, Onyebuchi A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Human Immunodeficiency Virus sero-discordance is high among heterosexual couples in Africa. However, only few studies have explored the factors that are associated with the prevalence in sub-Saharan Africa. The aim of this study was to determine the prevalence of female sero-discordance among HIV positive pregnant women in Owerri and to assess its possible associated factors. Methods: A cross sectional study of pregnant women (and their partners) who tested positive to HIV I and II at the Prevention of Mother to Child Transmission (PMTCT) clinic from December 2015 to May 2016 in Federal Medical Center Owerri, Imo state, Nigeria. Results: A total of 106 HIV positive pregnant women (and their partners) were studied. The prevalence of female serodiscordance was 63.2% (67/106). Pre-marital serodiscordance contributed about 52.2% (35/67) female serodiscordance among couples in the study. Sero-discordance rate for the lower, middle, and upper classes were 50% (28/56), 76.1% (35/46) and 100% (4/4) respectively and was statistically significant (p<0.01). Condom use was significantly associated with female serodiscondance (P<0.01). CD4+ count of the female partner at booking was also found statistically significantly associated with female serodiscordance (P<0.01). Conclusions: There is high prevalence of female serodiscordance among HIV positive pregnant women in Owerri. Pre-marital serodiscordance contributed significantly to high level of female serodiscordance among couples. Higher social class, condom use and high female- partner CD4+ count are significantly associated with female sero-discordance.